2016
DOI: 10.5327/z1679-443520164615
|View full text |Cite
|
Sign up to set email alerts
|

Absenteísmo-doença no serviço público municipal da Prefeitura Municipal de Vitória

Abstract: | Context:Knowing the diseases that lead to leave of absence is important for the development of measures capable of creating the conditions for a safer and more pleasant working environment for the workers, which may reduce sickness-absenteeism index. Objective: To identify the causes of sickness-absenteeism among municipal civil servants in Vitória (Espírito Santo, Brazil) in 2012. Methods: This is a descriptive and retrospective epidemiological study based on information disclosed by the Office of Occupatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
1
11

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 7 publications
3
10
1
11
Order By: Relevance
“…Other studies corroborate these results (26)(27)(28)(29) . An epidemiological research held in Vitória (ES) in a database of the Occupational Medicine Department revealed mixed anxiety-depressed disorder as prevalent (6.34%) and with the longest average duration (23.6 days) of the period of absence from work out of the causes for sick leave due to anxiety disorders (30) .…”
Section: Discussionmentioning
confidence: 99%
“…Other studies corroborate these results (26)(27)(28)(29) . An epidemiological research held in Vitória (ES) in a database of the Occupational Medicine Department revealed mixed anxiety-depressed disorder as prevalent (6.34%) and with the longest average duration (23.6 days) of the period of absence from work out of the causes for sick leave due to anxiety disorders (30) .…”
Section: Discussionmentioning
confidence: 99%
“…16 The absence rates calculated by national and international studies range from 3 to 9.7% depending on the occupation and the characteristics of the health care service. 7 , 8 , 10 - 12 …”
Section: Discussionmentioning
confidence: 99%
“… 1 , 2 , 7 Therefore, the workers’ relationship to their job, combined with the high demands for productivity, exert an influence that goes beyond the work environment and relationships, and ultimately affects both personal and health-related factors. 7 , 8 …”
Section: Introductionmentioning
confidence: 99%
“…PAE age also has an infl uence on their health, aff ecting absenteeism. Being part of the older group of workers constitutes a moderated risk factor in terms of belonging to the sick list, which is backed up by other reports (Bastos, Saraiva & Saraiva, 2016;Sundstrup et al, 2018). Age and motivation in the public sector are also related.…”
Section: Specifi C Factors Related To the Employee Absenteeism In Thementioning
confidence: 95%